Carvedilol-?-cyclodextrin Systems: Preparation, Characterization and in vitro Evaluation - Sharma, Anshu; Jain, CP (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The purpose of this study was to improve the solubility and dissolution rate of carvedilol by forming a complex with ?-cyclodextrin. Phase solubility diagrams revealed increase in solubility of the drug upon cyclodextrin addition, showing AN type curve. Complexation of carvedilol was carried out with ?-cyclodextrin by physical mixing, kneading and co-precipitation method. The prepared complexes and physical mixture were characterized by Fourier transform infra red spectroscopy, differential scanning calorimetry, powder X-ray diffractometry and inclusion efficiency. It was also observed that the complexes exhibit higher dissolution rates than the pure drug and physical mixture. Among all carvedilol-cyclodextrin complexes, inclusion complex (1:5) prepared by co-precipitation method showed better release. Dhaka Univ. J. Pharm. Sci. 12(1): 51-58, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16300